Poecilia sphenops Valenciennes, 1846 (Cyprinodontiformes, Poeciliidae): new record in rio Sergipe basin, northeastern Brazil - Brito, Marcelo Fulgêncio Guedes de (2013)
The present paper reports the first record of non-native species Poecilia sphenops Valenciennes, 1846 in northeastern Brazil in rio Sergipe basin, a coastal drainage of the Sergipe state. This species was collected at seven sites in the Caatinga biome. The cause of the introduction is not known, but we believe it is a direct impact of the aquarium trade through the aquarium dumping performed by hobbyists. The presence of P. sphenops in natural waterbodies increases concerns for interference with native ecosystems, and the risk of eggs predation in native species with low fecundity and absence of parental care such as Astyanax lacustris and Serrapinnus heterodon, competition and hybridization with the native poeciliid Poecilia vivipara.